Implementation, Control Of Management Audit On The Performance Of The Regional Drinking Water Company (PDAM) Palopo City - Dangkeng, Arianto; Nurfaisah, Nurfaisah; Wally, Achyar Adya (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
Implementation of Management Audit at Regional Water Company (PDAM) Palopo City This research was conducted in order to find out how the management audit process at PDAM Palopo City. This research was carried out using a descriptive analysis case study method, which is a method that collects, presents and analyzes. The collection of research material is carried out by taking financial data and distributing questionnaires so that it will obtain a fairly clear picture of an object under study. From the research that was faced by the author, there were not a few obstacles the author got, including data access and free time for interviews. The research results obtained are as follows; The planning managed by the company has been effective, but in operating control it is seen that it still needs careful evaluation. Productivity has been adequate in distributing raw materials in the form of water seeds and has met service standards. The level of inventory or reserves has been adequate but in the consumer service sector it is still considered less than optimal so it is recommended for company management to evaluate it as an internal control. The most sensitive thing is in the budget or financial sector. The results were less than optimal, especially in the income sector which decreased compared to last year.